Studying α-Synuclein pathology using iPSC-derived dopaminergic neurons - Zambon, F (2017)
Parkinson's disease (PD) is characterised by the loss of dopaminergic neurons in the Substantia Nigra pars compacta in the midbrain and the presence of intracellular aggregates, known as Lewy bodies (LBs), in the surviving neurons. The aetiology of PD is unknown but a causative role for α-Synuclein (SNCA) has been proposed. Although the function of αSyn is not well understood, a number of pathological mechanisms associated with αSyn toxicity have been proposed. In this study, nine induced pluripotent stem cells (iPSCs) lines from healthy individuals and PD patients carrying the A53T SNCA mutation or a triplication of SNCA were differentiated to dopaminergic neurons (iDAn). All iPSC lines differentiated with similar efficiency to iDAn, indicating that they could be used for phenotypic analysis. Quantification of αSyn expression showed increased αSyn intracellular staining and the novel detection of increased αSyn oligomerization in PD iDAn. Analysis of mitochondrial respiration found a decrease in basal respiration, maximal respiration, ATP production and spare capacity in PD iDAn, but not in undifferentiated iPSCs, indicating the cell-type specificity of these defects. Decreased phosphorylation of dynamin-1-like protein at Ser616 (DRP1Ser616) and increased levels of Peroxisome proliferator-activated receptor gamma coactivator 1-α (PGC-1α) in A53T SNCA iDAn suggest a new pathological mechanism linking αSyn to the imbalance in mitochondria homeostasis. Markers of endoplasmic reticulum (ER) stress were found to be up-regulated, along with increased β- Glucocerebrosidase (GBA) activity, perturbation of autophagy and decreased expression of fatty acids binding protein 7 (FAPB7) in PD iDAn. Lastly, lentiviral vectors for RNAi-mediated knockdown of αSyn were developed and these reduced αSyn protein levels in iDAn, resulting in increased expression of FABP7. These results describe a novel functional link between αSyn and FABP7. This work demonstrates that iDAn are a promising and relevant in vitro cell model for studying cellular dysfunctions in PD pathology, and the phenotypic analysis of A53T SNCA and SNCA triplication iDAn enabled the detection of novel pathological mechanisms associated with PD.